Development of a Marine-Based E-Module in Grenden Village to Enhance Science Literacy of Junior High School Students - Sri Wahyuni; Aisyah Emelia Ismawati; Rizka Elan Fadilah; Friny Napasti (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
Development of a Marine-Based E-Module in Grenden Village to Enhance Science Literacy of Junior High School Students. The purpose of this study was to examine the content validity, construct validity, and response to improve students' science literacy. The development of an e-module based on marine potential for the material of plant and animal reproduction systems is based on the consideration of students to get learning experiences by utilizing the surrounding environment and being aware of preserving the marine environment. The research method used was the ADDIE development design consisting of three stages, namely analysis, design, and development. The results showed that (1) the percentage of content validity of the e-module based on marine potential was 85%, (2) the percentage of practicality of the e-module based on marine potential was 90% with an N-gain of 0.77, (3) the percentage of response to the e-module based on marine potential was 76%, so it can be concluded that the e-module based on marine potential is valid in terms of content and construct with a positive response to improve junior high school students' science literacy.